A novel natural coating for food preservation: Effectiveness on microbial growth and physicochemical parameters. (May 2019) - Carocho, Marcio; Heleno, Sandrina; Rodrigues, Paula; Barreiro, M. Filomena; Barros, Lillian; Ferreira, Isabel C.F.R.
Abstract: This work describes the development of a sustainable and natural coating solution based on iota-carrageenan and rosemary extract intended to preserve cooked ham through dipping. Upon comparing the physical and microbial load changes between this solution and the traditional plastic wrap along 15 consecutive days, the results showed that in terms of microbial load the samples treated with the developed solution had a lower microbial count. Furthermore, only slight changes in moisture loss and hardness were observed between samples using the two tested preservation strategies. Colour analysis revealed that dipped samples presented reduced lightness, with a tendency to avoid shifting to a blue tone over the 15-days of storage. This work indicates that natural polymers combined with natural antimicrobials and antioxidants can be employed to reduce the dependence on synthetic polymers and offer feasible solutions to be applied at an industrial level. Highlights: Carrageenan and rosemary extract were used as a dipping food coating for ham. The microbial load along storage time was lower for the dipped samples. Hardness was increased overtime for the dipped samples. Some changes in the external color among samples during storage time of 15 days. Bio-based food coatings can be alternatives to plastics for food conservation.